2022
DOI: 10.1002/mren.202200007
|View full text |Cite
|
Sign up to set email alerts
|

Toward Bio‐Sourced Elastomers with Reactive/Polar Groups. Myrcene – Glycidyl Methacrylate Copolymerization: Reactivity Ratios, Properties, and Preliminary RAFT Emulsion Polymerization

Abstract: There is a pronounced need of replacing fossil-origin materials with sustainable ones. Myrcene (Myr) is a biobased terpene-type monomer derived from diverse plants that is a potential substitute for diene monomers (e.g., butadiene), in the manufacture of elastomers. Here, the copolymerization of Myr with glycidyl methacrylate (GMA) is studied as a candidate route for producing functional/polar elastomers. Reactivity ratios (RR) for this system are estimated using the error-in-variables method resulting in r My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
(86 reference statements)
1
8
0
Order By: Relevance
“…The Myr/GMA copolymerization was studied previously using nitroxide-mediated polymerization (NMP) and reversible addition−fragmentation chain-transfer polymerization (RAFT) and reactivity ratios of the two monomers were estimated by various methods, assuming a terminal copolymerization model. [36,37] Reactivity ratios for Myr and GMA by nitroxide-mediated radical polymerization (NMP) were reported as r Myr = 0.49 ± 0.13 and r GMA = 0.50 ± 0.13 with 95% confidence bounds, [31] and also reactivity ratios of r Myr = 0.5181 ± 0.0620 and r GMA = 0.3009 ± 0.0141 were reported using RAFT polymerization. [37] These estimates serve as guides for the microstructures we expect for the precursors.…”
Section: Effect Of Feed Composition On My/gma Copolymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Myr/GMA copolymerization was studied previously using nitroxide-mediated polymerization (NMP) and reversible addition−fragmentation chain-transfer polymerization (RAFT) and reactivity ratios of the two monomers were estimated by various methods, assuming a terminal copolymerization model. [36,37] Reactivity ratios for Myr and GMA by nitroxide-mediated radical polymerization (NMP) were reported as r Myr = 0.49 ± 0.13 and r GMA = 0.50 ± 0.13 with 95% confidence bounds, [31] and also reactivity ratios of r Myr = 0.5181 ± 0.0620 and r GMA = 0.3009 ± 0.0141 were reported using RAFT polymerization. [37] These estimates serve as guides for the microstructures we expect for the precursors.…”
Section: Effect Of Feed Composition On My/gma Copolymerizationmentioning
confidence: 99%
“…[36,37] Reactivity ratios for Myr and GMA by nitroxide-mediated radical polymerization (NMP) were reported as r Myr = 0.49 ± 0.13 and r GMA = 0.50 ± 0.13 with 95% confidence bounds, [31] and also reactivity ratios of r Myr = 0.5181 ± 0.0620 and r GMA = 0.3009 ± 0.0141 were reported using RAFT polymerization. [37] These estimates serve as guides for the microstructures we expect for the precursors.…”
Section: Effect Of Feed Composition On My/gma Copolymerizationmentioning
confidence: 99%
“…NMP with BlocBuilder was used to control the molecular weight of the prepolymers and minimize possible side reactions and cross-linking of Myr during the polymerization. Copolymerizations of Myr using reversible-deactivation radical polymerization (RDRP) have been reported. ,, For example, Pablo-Morales et al and Hilschman et al utilized reversible addition–fragmentation chain-transfer (RAFT) for the copolymerization of Myr with GMA and styrene, respectively. , Métafiot et al showed effective copolymerization of Myr with methacrylates, such as IBOMA and GMA, with high regioregular microstructures using NMP. ,, Herein, NMP was adopted since it does not rely on sulfur-based chain-transfer agents or any metallic ligands. , This is particularly important since the thiocarbonylthio chain-transfer agent moieties in RAFT are prone to rapid aminolysis upon treatment with primary amines and therefore chain end modification is required before further processing. , …”
Section: Resultsmentioning
confidence: 99%
“…30,32,52 For example, Pablo-Morales et al and Hilschman et al utilized reversible addition−fragmentation chain-transfer (RAFT) for the copolymerization of Myr with GMA and styrene, respectively. 53,54 Metafiot et al showed effective copolymerization of Myr with methacrylates, such as IBOMA and GMA, with high regioregular microstructures using NMP. 37,41,55 Herein, NMP was adopted since it does not rely on sulfurbased chain-transfer agents or any metallic ligands.…”
Section: Prepolymer Synthesis and Characterizationmentioning
confidence: 99%
“…Saldívar-Guerra and his coworkers (Fig. 13c) 82 have developed the RAFT copolymerization of β-myrcene and glycidyl methacrylate (GMA) using CDSPA (4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid) as chain transfer agent and potassium persulfate as radical initiator, under aqueous emulsion polymerization conditions and using semi-continuous addition of the monomers to prepare a bio-based elastomer (monomer conversion in the range of 74–92%). They determined the reactivity ratios of the monomers, and studied the effect of the β-myrcene concentration over the molar mass of the copolymer, as well as the microstructure of the copolymers (predominance of 1,4- cis ) (polymerizations in bulk and in toluene solution with a monomer conversion lower than 20%).…”
Section: Terpene-based Polymersmentioning
confidence: 99%